Development of Interactive Wordwall-Based Media to Enhance Letter Symbol Recognition Ability in Children Aged 5–6 Years - Zuyyina Kamila; Nurul Khotimah; Dhian Gowinda Luh Safitri; Dewi Komalasari (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Language development is a crucial aspect that must be supported by the child’s environment, including school, family, and society. Observations at TK Aisyiyah 02 Surabaya showed that some children still struggle to recognize similar-looking letters such as b, d, m, and n. The learning media used were limited and the monotonous teaching methods made children easily bored and less focused. This study aims to develop an interactive learning media using Wordwall, based on the ADDIE development model. The media was designed as an engaging game including letter recognition, matching letters with pictures, and letter sound pronunciation. Validation results showed that the media is highly feasible, with a material expert score of 89.29% and a media expert score of 92.5%. Practical teacher interviews also confirmed that the media is suitable for early childhood learning styles, supporting visual and auditory learning, and increasing children's enthusiasm and focus. The trials were conducted using a one-group pretest-posttest design on two small groups. The Shapiro-Wilk normality test showed that the data were not normally distributed, leading to the use of the Wilcoxon test. The Wilcoxon test result showed a significance value of 0.001 (p < 0.05), indicating a significant difference between the pretest and posttest scores. Learning improvements were also evidenced by the N-Gain Score of 0.86 in class B1 and 0.88 in class B2, both categorized as high. Thus, the interactive media based on wordwall proved to be effective in improving the ability to recognize similar-looking letters in early childhood through a play-based learning approach.